Budget deficit in the early Islamic history: a review of the literature and examination of the historical evidence - Said Al Salmani, Said Rashid; Syed Azman, Syed Marwan Mujahid (Springer, 2024)
This paper explores the issue of budget deficit in the early days of Islam, particularly during the era of the Prophet Muhammad and his companions. The paper reviews the literature on this topic and analyses the sources and uses of public revenues and expenditures, as well as the situations where the Islamic state faced deficits and how they were financed. The paper identifies four instruments of financing deficits that were used in the early days of Islam: public loans, paying Zakah in advance, setting up a reserve fund, and paying Altawzif (taxes). The paper analyzes the conditions and rules that govern each instrument and compares them with the modern concepts of budgeting and taxation. The paper concludes that the early Islamic state had a streamlined and flexible budget system that was able to cope with various challenges and achieve economic and social objectives.